Inovasi Pembelajaran: Media Diorama Untuk Peningkatan Kosakata Bahasa Inggris di Mi Fathul Jannah - Hesty Widiastuty; Nazwa Maulani Dewi; Siti Nurrahmah; Yulis Setiawati; Muhammad Hidayatur Rahman; Ayu Putriana Lestari; Ahmad Basahil (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
In the current globalized world, learning English is essential for teachers and students in Indonesia to develop effective teaching strategies. Engaging edducational media, like diorama, can increase students' comprehension and focus when learning English. This community outreach is being carried out at MI Fathul Jannah to promote the use of dioramas in English language instruction. The method that is used is called "Service Learning," which involves observation, execution, and assessment. This activity involves discussion and debate about family members as well as interactive activities like spelling bees, translation, and matching features. The results indicate an increase in the understanding of kosakata, teamwork, and self-awareness among the learners in English. Even if there are time constraints, using a diorama as an innovative and interactive teaching tool works very well. This exercise is intended to serve as a guide for teachers to adopt the method.